EFEKTIVITAS PENGGUNAAN MACROMEDIA FLASH PRO 8 MATERI USAHA DAN PESAWAT SEDERHANA TERHADAP HASIL BELAJAR PESERTA DIDIK SMP NEGERI 3 PONTIANAK - Ricky, Ricky; Sahala, Stepanus; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the effectiveness of using Macromedia Flash Pro 8 on business materials and simple machines on student learning outcomes at SMP Negeri 3 Pontianak. The form of this research is a pre-experimental design with a one group pretest-posttest design. Data collection techniques used measurement techniques, carried out by collecting test results given before and before treatment (treatment). Data analysis was carried out with the help of SPSS for descriptive analysis and Wilcoxon test, then effect size analysis. The results showed that (1) the students' learning outcomes at the pretest were 7.44 and increased by 1.2 after treatment to 8.64 at the posttest. (2) Data analysis using the Wilcoxon test showed a p value (Asymp. Sig 2) of 0.001 which was smaller than the threshold of 0.05 (p 0.05) this indicates that there is a difference between pretest and posttest so that it can conclude the use of macromedia flash pro 8 has an effect on student learning outcomes. (3) The use of macromedia flash pro 8 is effective in improving student learning outcomes. Based on the calculation of the effect size, Cohen's obtained an effect size value of 0.91 which is included in the high category. So that the results of this study are expected to be a consideration for schools and teachers in choosing effective learning media to improve student learning outcomes.